An introduction to game theory - Osborne, Martin J. (Oxford University Press, 2004)
An exposition of modern game theory suitable for advanced undergraduates, this book emphasizes the ideas behind the theory rather than their mathematical expression. It covers strategic, extensive, and coalitional games, and includes the topics of repeated games, bargaining theory, and evolutionary equilibrium.